2015
DOI: 10.1155/2015/504043
|View full text |Cite
|
Sign up to set email alerts
|

Blast-Induced Damage on Millisecond Blasting Model Test with Multicircle Vertical Blastholes

Abstract: To investigate the blast-induced damage effect on surrounding rock in vertical shaft excavation, 4 kinds of millisecond blasting model tests with three-circle blastholes were designed and carried out with excavation blasting in vertical shaft as the background. The longitudinal wave velocity on the side of concrete model was also measured before and after blasting. Then blast damage factor was then calculated by measuring longitudinal wave velocity before and after blasting. The test results show that the blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The test results are in good agreement with those of numerical simulation, indicating that the pressure-relief effect of the borehole can protect the wall materials and the bottom air gap columns. Ma et al [21] tested 4 types of millisecond blasting models with three-circle boreholes, aiming to find the blast damage on the surrounding rock in vertical shaft excavation and put forward effective damage control measures. Zhao et al [22] performed a blasting model test with similar materials and dosages by Froude scaling and provided theoretical and empirical references to the selection of materials and charging conditions for blasting test models.…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…The test results are in good agreement with those of numerical simulation, indicating that the pressure-relief effect of the borehole can protect the wall materials and the bottom air gap columns. Ma et al [21] tested 4 types of millisecond blasting models with three-circle boreholes, aiming to find the blast damage on the surrounding rock in vertical shaft excavation and put forward effective damage control measures. Zhao et al [22] performed a blasting model test with similar materials and dosages by Froude scaling and provided theoretical and empirical references to the selection of materials and charging conditions for blasting test models.…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…Ma Q.Y. et al [17,18] designed several sets of blasting model tests and a blasting plan ensuring the cutting effect was obtained. Liu D.W. et al [19,20] conducted rock-like material model tests, and the non-linear change law of rock mass damage and the advantages of V-shaped grooves were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…General Particle Dynamics (GPD) method was put forward to study the zonal disintegration mechanism of deep rock mass in blasting excavation, and it was found that dynamic loads and high geostress are two dominant factors for occurrence of zonal disintegration [30]. Blasting excavation not only applies a dynamic load on deep rock masses but also induces blasting damage around an excavation [31,32]. By considering both high axial geostress and blasting load in deep rock masses, failure mechanism of zonal disintegration is investigated by elastic stress field analyses and modified Hoek-Brown criterion.…”
Section: Introductionmentioning
confidence: 99%